Cultural Ideology in Translating Salatiga Legend Stories and Their Implication in Teaching Translation - Tri Astuti (English Education Study Program Faculty of Teacher Training and Education, 2019)
The folklore of the Salatiga legend needs to be disseminated in the archipelago so that these cultural values ??can be understood by people from various ethnic groups in Indonesia using Indonesian. In the process of translating the legend (from Javanese Krama into Indonesian) it is necessary to have an appropriate translation method so that the message to be conveyed in the source language (BS) matches the target language (BT). This research aims to investigate the translation method used in the Salatiga Legend and explore the cultural ideology that affects the translator in translating the Salatiga Legend. In this research, only the translation of the word or phrase which is related to the translation is examined. This research is a descriptive qualitative research with content analysis method. Data processing techniques using literature study, see, and note. To test the validity of the data in the study used triangulation models, namely data triangulation, theory triangulation, and expert triangulation. The results of the research are the dominant translation methods used are equality and borrowing, while the transposition method is not found. The finding, translation methods used by translators in the Salatiga Legend story, especially those relating to the translation units of words and phrases of objects, are dominated by the equality method. In this study also no transposition method was found.